2018
DOI: 10.3168/jds.2018-15151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrous expression on timing and failure of ovulation of Holstein dairy cows using automated activity monitors

Abstract: The aim of this study was to determine if estrous expression, as measured by an automated activity monitor (AAM), affects timing and failure of ovulation of lactating Holstein dairy cows. Cows were equipped with 2 AAM, 1 neck-mounted (AAM C) and 1 leg-mounted (AAM L), by 10 d postpartum and enrolled into the trial when their activity crossed the alert threshold on the AAM C. A total of 850 episodes of estrus from 293 different cows were used for this study. When cows were enrolled, their ovaries were scanned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 45 publications
3
46
2
Order By: Relevance
“…Although not tested in this study, previous reports arising from our laboratory using similar AAM have demonstrated that greater estrous expression is associated with higher fertility (8,24,25) and lower anovulation rates (12,26). Greater estrous expression in the current study was found to generate higher positive amplitude changes in temperature at estrus but have smaller increases in temperature around ovulation than cows with lesser estrous expression when under low THI conditions.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Although not tested in this study, previous reports arising from our laboratory using similar AAM have demonstrated that greater estrous expression is associated with higher fertility (8,24,25) and lower anovulation rates (12,26). Greater estrous expression in the current study was found to generate higher positive amplitude changes in temperature at estrus but have smaller increases in temperature around ovulation than cows with lesser estrous expression when under low THI conditions.…”
Section: Discussioncontrasting
confidence: 40%
“…The cows used in the present study were a subset of animals initially described in a companion study (12). To be included in the present study cows had to be 30 DIM, had an estrus alert on the AAM, and be equipped with a rumen-reticular temperature bolus.…”
Section: Animals and Housingmentioning
confidence: 99%
“…Exclusive of technical errors, a cow inseminated at estrus can fail to become pregnant with a viable embryo at day 7 of development either because of anovulation, fertilization failure, or early embryonic death. Estimates of the incidence of anovulation at estrus in lactating dairy cows range from 3.4% to 6.7% ( López-Gatius et al, 2005 ; Valenza et al, 2012 ; Burnett et al, 2018 ) except during heat stress when the incidence has been reported to increase to 12.4% ( López-Gatius et al, 2005 ). Estimates of the incidence of ovulation failure in beef cattle were 2% for taurine heifers ( Diskin and Sreenan, 1980 ) and 14% for both non-suckled cows and heifers that were largely Brahman crosses ( Warnick and Hansen, 2010 ).…”
Section: Sources Of Pregnancy Failure Avoided Using Embryo Transfermentioning
confidence: 99%
“…(2013) found that cows with STAT5A allele G showed greater in-stall estrus expression, which can also be due to increased production of estradiol in the follicle. Greater estrus expression is associated with greater fertility and improved CFHI, DO, and SPC ( Burnett et al., 2018 ). We propose that future studies include larger numbers of animals and involve the measurement of hormones involved in the growth hormone metabolic pathway to determine the full effect of STAT5A on reproductive performance.…”
Section: Discussionmentioning
confidence: 99%